Optimal control of fair discrete-event systems - Li, Yonghua (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, we formulate and solve a class of optimal control problems for discrete-event systems modelled as finite-state automata. The controlled discrete-event system is considered optimal if the performance index consisting of a behaviour gain and a control cost is maximized, plus that the controller satisfies a structural constraint. A hybrid computational algorithm is devised to reduce the solution space for the optimal controller design. An example is given to illustrate the results.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka